Hofmannsthal, Rückert und Rūmī – zum Ghasel «Für Mich ...» (Studia theodisca, 2013)
The following paper analyses Hugo von Hofmannsthal’s ghazal «Für mich ...». It identifies for the first time Friedrich Rückert’s ghazal «Ich bin das Sonnenstäubchen ...» – an original poem only vaguely reminiscent of Djalāl-od-Dīn Rūmī’s Diwan – as the source of Hofmannsthal’s text. The comparison shows how Hofmannsthal introduces a pronounced metapoetic dimension while adapting distinguishing features of Rückert’s poem, such as the oxymoronic style and the recurrent use of the first person. In Hofmannsthal’s poem Rückert’s monistic merging of the self with nature gives way to an artistic re-shaping of everyday reality by the aesthete.